Evolutionary and Ecological Explanations for the Elevational Flexibility of Several East African Bird Species Complexes - Fjeldså, Jon; Bowie, Rauri C. K. (Frontiers in Ecology and Evolution, 2021)
Africa’s montane areas are broken up into several large and small units, each isolated as forest-capped ‘sky islands’ in a ‘sea’ of dry lowland savanna. Many elements of their biota, including the montane forest birds, are shared across several disjunct mountains, yet it has been difficult to rigorously define an Afromontane forest avifauna, or determine its evolutionary relationships with the birds of the surrounding lowland forests. In order to trace the historical relationship between lowland and highland avifaunas, we use phylogeographic methods to explore the genetic relationships between local populations of avian lineages that are resident both in highlands and in lowland forests within the biodiversity hotspot of eastern Africa. The study reveals some idiosyncratic patterns, but also a prominent number of cases of geneflow between populations in southern areas, mainly around the Malawi Rift, and mountains and coastal forests close to the equator. This may reflect more continuous past distributions through northern Mozambique and coastal Tanzania, or seasonal migrations between areas with different rainfall regimes. Over time, this appears to result in a higher persistence of lineages, and an accumulation of species representing forest-dependent lineages within the Eastern Arc Mountains of Tanzania and the northern part of the coastal forest mosaic.